Investigation of the Nonthermal X-Ray Emission from the Supernova Remnant CTB 37B Hosting the Magnetar CXOU J171405.7-381031 - Chanho Kim; Jaegeun Park; Hongjun An; Kaya Mori; Stephen P. Reynolds; Samar Safi-Harb; Shuo Zhang (The Astrophysical Journal)
We present a detailed X-ray investigation of a region (S1) exhibiting nonthermal X-ray emission within the supernova remnant (SNR) CTB 37B hosting the magnetar CXOU J171405.7−381031. Previous analyses modeled this emission with a power law (PL), inferring various values for the photon index (Γ) and absorbing column density ( N _H ). Based on these, S1 was suggested to be an SNR shell, a background pulsar wind nebula, or an interaction region between the SNR and a molecular cloud. Our analysis of a larger data set favors a steepening (broken or curved PL) spectrum over a straight PL, with the best-fit broken power-law (BPL) parameters of Γ = 1.23 ± 0.23 and 2.24 ± 0.16 below and above a break at 5.57 ± 0.52 keV, respectively. However, a simple PL or srcut model cannot be definitively ruled out. For the BPL model, the inferred N _H = (4.08 ± 0.72) × 10 ^22 cm ^−2 towards S1 is consistent with that of the SNR, suggesting a physical association. The BPL-inferred spectral break ΔΓ ≈ 1 and hard Γ can be naturally explained by a nonthermal bremsstrahlung (NTB) model. We present an evolutionary NTB model that reproduces the observed spectrum, which indicates the presence of subrelativistic electrons within S1. However, alternate explanations for S1, an unrelated PWN or the SNR shock with unusually efficient acceleration, cannot be ruled out. We discuss these explanations and their implications for gamma-ray emission from CTB 37B and describe future observations that could settle the origin of S1.